EFFECT OF VISCOSITY ON THE DIFFUSION MIXING PROCESS IN ISOTHERMAL MULTICOMPONENT GAS MIXTURES - Oteuova Ұ.Д.; Alpeissova А.Д.; Asembaeva М.К.; Nurmukhanova А.З. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
In this article, the influence of viscosity on the stability of the diffusion process in isothermal multicomponent gas mixtures is experimentally studied. For gas systems 0,4300 C3H8 + 0,5700 He - 0,4300 C3H8 + 0,5700 CH4 and 0,4300 С3Н8 + 0,5700 Не - 0,4200 C3H8 + 0,5800 Ne, the results of calculating the number of partial losses of components at different pressures are given. The dependence of the amount of diffused components (partial expenses) on the pressure for this initial composition was studied. Then, the characteristic features of mass transfer for systems with different viscosities were compared over the same time intervals. Studies have shown a qualitative change in the nature of the mixing process. An increase in the viscosity of the mixture led to a stabilization of the diffusion process with an increase in the pressure in one case and the time of the process in the other. Analysis of the results showed that the viscosity affects the nature of the diffusion instability of the gas mixing process.